Derechos humanos y virtudes fundamentales - Carlos Llano Cifuentes (Tópicos, 2013)
When establishing the human rights within a democratic constitucionalism instead of in the human person's truth, the legalisms enter into an infinite wheel. Then, it is necessary to settle them in a pre-legal foundation, previous to any deliberation that includes the classic virtues of the human coexistence which make any democratic process possible. Although this document centers basically in justice, success, courage and temperance, as hinge of all virtue, it also refers to the value of companionship, simplicity, austerity, loyalty, trust among others. But all this axiological frame forces us to look back naturally to the family where those rights are developed.